Predicting Financial Distress using Altman Z-Score, Springate S-Score and Zmijewski X-Score on Tobacco Companies in The Indonesia Stock Exchange - Ulfah, Hasna Kurnia; Moin, Abdul (Selekta Manajemen: Jurnal Mahasiswa Bisnis & Manajemen, 2022)
This study examines the use of three models of financial distress prediction namely Altman Z-Score, Springate S-Score and Zmijewski X-Score on the Tobacco Companies Listed in the Indonesia Stock Exchange. Further, the study tests the the accuracy of the three models to predict the bankruptcy of those companies. The sample consists of 5 firms with 25 observations for each model. To obtain the level of accuracy, the study categories the firms into distress or non-stress firms by comparing between return on equity (ROE) and Bank Indonesia (BI) rate. This study finds that the Springate S-Score model is the most accurate models to predict the bankruptcy of the Tobacco companies listed in the Indonesia Stock Exchange (IDX) by 80%.